NILAI SEWA RUKO DUA LANTAI DAN ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DI KOTA DENPASAR - , Putu Yovina Sari Parthady ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the two-storey shophouse rental values and the factors that influence in Denpasar. characteristic of the store factors are land area, building area, spacious parking and a dummy Balinese architectural design and location factors that road width, distance to modern shopping center, the distance to hotel, the distance to housing, the distance to tourism object, the distance to airport, the distance to elementary schools, the distance to center of worship. The data used in this study is primary data obtained from questionnaires spread to shop owners and renters in the city of Denpasar. This study uses cross section data using simple random sampling method and sample obtained 52 samples. The analytical tool used in this research is descriptive analysis, paired t test and linear regression analysis. Descriptive research results showed the average value of shophouses Rp1,014,851,00 per square meters shop with the lowest value of Rp187 500,00 per square meter and the highest Rp418 851,00 per square meters. Average shop building area is 272 m 2 with the lowest is 48 m 2 and the highest is 140 m 2 . The results of paired t test analysis is the value of the rental shop owner is greater than the value of rental shop if the respondent became the owner of the shop. The results of the regression analysis showed that the variable physical characteristics shop area of land, a building, outside parking and Balinese architectural design dummy positive and significant. Variable location of road width, distance to hotel, the distance to airport have positive and significant effect. Distances from residential locations, the distance to housing and the distance to the elementary school and a significant and negative effect.